Grigore Vieru – the Poet of Values: poet; issues; the Danube; culture; values - Baltatu, Ludmila (Journal of Danubian Studies and Research, 2023)
Grigore Vieru is the poet of the Romanian thinking and sensation. His creations are an echo of the dominant ideas of our national consciousness. In Vieru’s writings there are expressed all our soul stirrings, all our quotidian worries. The veneration of the sacred mother - a symbol of all the beginnings, of the eternity, of the motherland and of the homeland – is one of the main motives of Grigore Vieru’s creation. Therefore, mother in Vieru’s verses represents a model of patience in face of all the vicissitudes of life, a historic prototype of the nation’s courageous fight and a calm sense of the destiny. Grigore Vieru’s literary creation is rich, embracing great themes and issues and being repre-sentative for the national culture. The nature’s beauties of the native homeland are exceptionally expressed with the Poet’s genuine warmth. In Vieru’s verses the Prut and Danube rivers hold a special place: on the Prut banks his childhood was spent and the Danube – the witness of the glorious historic events of our nation, an inexhaustible source of beauty and wealth.